Anaphoric resources in expository texts produced by children: the impact of a didactic sequence - Sánchez, Verónica; Plana, María Dolores; Benítez, María Elena (Colombian Applied Linguistics Journal, 2013)
This paper aims to explore the incidence of didactic strategies on the usage of anaphoric resources, in written expository texts, produced by Spanish speaking children, from Córdoba, Argentina. In order to identify and analyze the anaphoric resources used by children, we designed and implemented a sequence of didactic activities, based on gender textual characteristics. The genre to teach was the “encyclopedia entry”. We analyzed the children production obstacles and difficulties and compared the productions before and after the didactic intervention, in order to assess the impact of teaching in the development of the cohesion devices. Eighty Spanish speaking children, of 3rd grade who attended two schools from Córdoba, Argentina, participated in this study. The results showed consistent changes after the didactic intervention that mainly consisted in an increase of the diversity of resources and the adequacy score in final productions; a higher presence of lexical resources, a higher precision and a decrease of ambiguous ellipsis.